Die swyggebod van 1 Korintiers 14:34-35 weer eens onder die loep - Toit, Andries Bernardus du (HTS teologiese studies, 2001)
The taceat mulier of 1 Cor 14:34-35 revisited. Discussions of the role of women in the church's ministry, as well as feminist attacks on Paul, require that the debate on 1 Corinthians 14:34-35 should continue. The latest attempt to solve the clash between 1 Corinthians 11:2-16 and 14:34-35 by text-critical means is discussed and various harmonizing efforts are criticized. Also the expedient of putting the taceat in the mouth of an opposing party is found unconvincing. Paul's theology and especially his view of women in the ministry, indicate that 1 Corinthians 14:33b-36 should be viewed as a post-Pauline interpolation. The development of the different textual traditions was quite complex and includes various kinds of redactional activity. Ironical as it may seem, the identification of 1 Corinthians 33b-36 as a post-Pauline insertion brings us nearer to the original Pauline text than mere external text-critical considerations. However, the always imminent danger of subjectivity requires that this procedure be applied with great circumspection and only as a last option.